USE OF CRANBERRY EXTRACT AS AN ALTERNATIVE THERAPY IN A CAT WITH UROLITHIASIS AND SINISTER UNILATERAL HYDRONEPHROSIS: A CASE REPORT - Ni Kadek Puspa Dewi; Putu Devi Jayanti; I Putu Gede Yudhi Arjentinia; I Wayan Nico Fajar Gunawan (Fakultas Kedokteran Hewan Universitas Udayana, 2026)
Cranberry (Vaccinium macrocarpon) extract contains proanthocyanidins (PACs), anthocyanins, and flavonols, which act as antioxidants that protect kidney tissue through antioxidant activity and reduced oxidative stress and proinflammatory cytokine production. Urolithiasis is a urinary tract disorder characterized by the formation of crystals, excess sediment, uroliths, or calculi, which can block urine flow, causing back pressure on the kidneys and leading to hydronephrosis. This case report discusses the management of a 4-year-old domestic male cat that exhibited clinical symptoms of urinary tract obstruction and straining. Clinical signs of urinary tract obstruction were observed for one week. The diagnosis was made based on history, clinical signs, hematology, blood chemistry, urinalysis, and ultrasonography. Hematology examination results indicated lymphocytosis, granulocytopenia, and thrombocytopenia, while blood chemistry showed hypertotal proteinemia, hyperglobulinemia, and hypokalemia. Urine chemistry analysis showed positive leukocytes, protein, pH 7.5, specific gravity 1.010, and urine microscopy revealed struvite crystals and calcium oxalate. Ultrasonography revealed hyperechoic crystal particles in the lumen of the urinary bladder and dilated left renal pelvis. This case was diagnosed as urolithiasis and unilateral left hydronephrosis. Therapy included urinary catheter placement, 0.9% physiological NaCl flushing, 250 mg cranberry extract q24h PO, and special diet for kidney problems. Evaluation showed clinical improvement marked by the absence of stranguria and oliguria, although urinary crystals and dilated left renal pelvis were still detected on ultrasound examination. The owner was advised to monitor the urinary tract through urinalysis and ultrasound periodically, implement a special diet for kidneys and adequate water intake.